Implementing label filters on a shared tree mobile multicast architecture - Singh, Jaipal; Veeraraghavan, P.; Singh, S. (IEEE Computer Society, 2005)
This paper describes an architecture that filters packets within a subset of nodes on an existing shared multicast tree. The path connecting the group of nodes that want to communicate privately on the existing tree was given a label. These labels are used to route one-to-one and group communication traffic for selected nodes on a multicast tree. Nodes connected to the tree but are not on this label path do not receive any filtered packets. This filter architecture reduces network resource waste by utilising the existing network resources on the multicast tree like quality of service (QoS). In this paper, we also describe how this architecture can be used for mobile communication when implemented in a shared tree mobile multicast architecture.